Challenges for Healthcare Workers Caring for COVID-19 Patients in Indonesia: A Qualitative Study. (7th December 2021) - Setiawan, Herley Windo; Pratiwi, Ika Nur; Nimah, Lailatun; Pawanis, Zulfayandi; Bakhtiar, Arief; Fauziningtyas, Rista; Ramoo, Vimala
COVID-19 pandemic raises various challenges faced by health workers in hospitals. This study explored strategies for overcoming challenges in caring for COVID-19 patients at hospitals in Indonesia based on healthcare workers' experience. In-depth interviews were employed with 28 healthcare workers (physicians and nurses) who were purposively sampled. Data were collected via phone and analysed using the Colaizzi method. Five following challenges were found: difficulties in working with personal protective equipment (PPE), offline training for handling Covid and using PPE not being implemented evenly for all health workers, physical and psychological fatigue, difficulties in carrying out health education and assessment towards patients and families, and limited resources to cope with the COVID-19 pandemic. Meanwhile, some barriers require support from the government, public and hospital managers. The information gained from research on the strategies for caring for COVID-19 patients can contribute to better preparedness for hospitals and health workers facing the COVID-19 pandemic.